REVIEW DAN EDUKASI ALAT PELINDUNG DIRI MASYARAKAT DESA DALAM PRAKTEKNYA MELINTASI PANDEMI COVID-19 - Hafnah Khilwatul Ilmi; Mohammad Syaiful Pradana; Istiqomah Istiqomah; Rifky Ardhana Kisno Saputra (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2021)
The purpose of this community service is to find out how the perception and provide education of the village community towards the use of personal protective equipment during the Covid-19 pandemic This community service uses the home visit counseling method. Before conducting counseling, the team conducted observations and interviews, it was found that people tended to lack awareness in implementing Health protocols including understanding how to use personal protective equipment properly and correctly such as masks, hand sanitizers, face shields and so on. Therefore, it is important to carry out this outreach activity to prevent the transmission of Covid-19 in the family and village environment. This activity is carried out by providing a simulation of the use of personal protective equipment according to the standards of the Ministry of Health of the Republic of Indonesia and an explanation of a clean and healthy lifestyle during the pandemic. In addition, the distribution of masks and hand sanitizer for free was also carried out. The results of the implementation of this community service activity increase public understanding in using personal protective equipment and are expected to reduce the risk of Covid-19 transmission in the community.